Obstetric violence and its multiple faces: analysis of possible impacts on women's health (Research, Society and Development, 2021)
Considered as a matter of public health, obstetric violence is characterized as any and all violent actions practiced against women at the time of pre-partum, childbirth and puerperium, which can occur in public or private health services, and its practice is verified by different violent acts, the main ones being physical, psychological and institutional. This study aimed to analyze the different forms of presentation of obstetric violence, as well as its possible implications for women's health. To this end, the study was developed based on bibliographical research, supported by theoretical references that addressed the theme of obstetric violence and the impacts on women's quality of life and health. From the research, it can be seen the need to reformulate practices in maternal and child care services, aimed at continuing education and health training for professionals, seeking to achieve the prevention or mitigation of obstetric violence, as well as the incorporation of practices humanized in childbirth and birth.